Predictive value of a nomogram model for adverse outcomes in very low birth weight infants with patent ductus arteriosus: A prospective study - Sun, Xuan; Chen, Ling; Gao, Jinzhi (Frontiers in Pediatrics, 2023)
Objective: To establish a nomogram model for patent ductus arteriosus adverse outcomes (PDAao) in very low birth infants incorporating markers of echocardiography and N-terminal pro brain natriuretic peptide (NT-proBNP), and to evaluate the predictive values of the model. Methods: A prospective study was conducted for very low birth weight infants who were admitted from May 2019 to September 2020. An echocardiogram and blood NT-proBNP test were carried out in the first 48 hours after birth, and the arterial duct remained open in all cases. Other data collected included clinical symptoms and infants’ characteristics. Nomogram model was established to predict risk of PDAao (including severe BPD, IVH, NEC or death). Validation was performed by C-index and calibration curve. Results: 82 infants were enrolled and divided into adverse outcome (AO) group and normal outcome (NO) group with each 41 cases. PDA diameter, PDA maximum flow velocity, left atrium diameter/aortic diameter (LA/AO) ratio and NT-proBNP were independently risk factors of PDAao and included in the nomogram model. The model presented good discrimination with a C-index value of 0.917(95% CI 0.859-0.975). And calibration curves showed that the predicted PDAao probability was consistent with the actual PDAao incidence. Conclusion: The nomogram model incorporating with PDA diameter, PDA maximum flow velocity, LA/AO ratio and NT-proBNP in the first 48 hours could early predict the later occurrence of PDAao in very low birth weight infants.